BITCOIN MINING CARBON FOOTPRINT - Kononova, Kateryna; Dek, Anton (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The theoretical framework of the study covers the formation and development of cryptoeconomics, as well as its impact on the environment. The term cryptoeconomics is used to refer to a new industry, which develops around cryptocurrencies and blockchain. Cryptocurrency mining consumes a lot of electricity. As of September 2019, the estimated annual electricity consumption was 78.93 TWh (with an electricity price of 0.05 USD). This model was used to create the Cambridge Bitcoin Electricity Index web service. If we assume that electricity for mining is generated at coal-fired power plants only, then knowing the energy consumption of bitcoin miners, we can estimate carbon dioxide emissions at the upper boundary. In this case, carbon dioxide emissions are about 80.43 million tons of CO2, which corresponds to 0.24% of the total emissions in the world. The aim of this work is to simulate carbon dioxide emissions caused by bitcoin mining, taking into account the regional distribution of miners and various sources of electricity that are used for mining. To achieve it, the following tasks were set: 1) the formation of a reasonable list of mining pools; 2) clarification of the geographical distribution of miners; 3) assessment of the distribution of mining capacities by region; 4) evaluation of air pollution by regions. The problem of increasing electricity consumption by the network of bitcoin (and other cryptocurrencies) miners and the corresponding environmental impact should be discussed with policymakers, industry participants and the general public. According to the proposed method for assessing the geographical distribution of mining using the traffic of mining pools web pages, carbon dioxide emissions is about 44.12 million tons per year (0.13% of global emissions), which is two times lower than the upper boundary estimate.